Exploring the mechanism of tetramethylpyrazine in the treatment of osteoarthritis based on network pharmacology - Li, Juncen; Song, Daiying; Li, Bohui; Wang, Yajie; Sun, Huilin; Li, Qinglin; Lin, Xiangming; Wang, Di; Zhou, Guangdong; Liu, Yu (Frontiers in Chemistry, 2024)
Background Osteoarthritis (OA) is the most common joint disease, which mainly damages articular cartilage and involves the whole joint tissue. It has the characteristics of long course, repeated symptoms and high disability rate, and the incidence trend is gradually increasing. Tetramethylpyrazine (TMP) is the main alkaloid active substance in Ligusticum wallichii, a traditional Chinese medicine, which has the effect of promoting blood circulation and dredging collaterals, and has a good effect on the treatment of early OA, but its molecular mechanism has not been fully clarified so far. Based on network pharmacology, molecular docking simulation and animal experiments, this study explored the target and molecular mechanism of TMP in the treatment of OA. Methods We used PubChem, SwissTargetPrediction, and PharmMapper databases to predict the molecular structure and potential targets of TMP. GeneCards and DisGeNET databases were used to predict the relevant targets of OA. Apply UniProt database to convert targets into unified gene names, and proofread and remove duplicate gene names. The intersection targets of TMP and OA obtained on venny2.1.0 website were submitted to the STRING database to construct a PPI network. CytoScape 3.8.2 software was used to analyze the PPI network and obtain the sub-network modules and 10 key targets. The intersection targets of TMP and OA were analyzed by Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment using DAVID 6.8 database. The intersecting targets of TMP and OA, the biological process of GO enrichment, and KEGG signaling pathway were imported into Cytoscape 3.8.2 software to construct the TMP-target-pathway network diagram. Use molecular docking technology to simulate the interaction between TMP molecules and key targets, and predict the binding mode and binding ability. Animal models of rabbit knee osteoarthritis were prepared, and magnetic resonance imager (MRI) and fluorescence quantitative PCR (RT-qPCR) were used to observe the effect of TMP in treating OA as well as the expression of key target genes. Results 585 potential targets of TMP, 3,857 potential targets of OA, and 49 intersecting targets of TMP and OA were obtained. The top 10 key target genes were obtained, in order of ranking: ALB, ESR1, IL10, CAT, F2, MPO, C3, CYP3A4, CYP2C9, ANXA1. GO and KEGG analysis implied that the key targets might act on OA by affecting endothelial cell permeability, peri-articular microcirculatory status, NETs production, activation of complement system and coagulation pathway, regulation of immune function of macrophages and T cells, and substance metabolism pathway in vivo, etc. The molecular mechanism might involve the formation of neutrophil extracellular trap, regulation of the actin cytoskeleton, complement and coagulation cascades, and T cell receptor signaling pathways, etc. Molecular docking simulations showed that the binding energy of IL10 and ANXA1 to TMP was greater than -5Kal/mol, but the other key target proteins showed better binding to TMP, and the binding energy was less than -5 kcal/mol. Animal experiments showed that TMP had a significant therapeutic effect on OA. The TMP group had significantly reduced knee joint effusion and bone marrow damage compared to the OA group (p < 0.05). The qRT-PCR results showed that compared with the OA group, the mRNA expression of ESR1, CAT, C3, CYP3A4, CYP2C9, and ANXA1 in the TMP group increased (p < 0.05), while there was no significant difference in mRNA expression of ALB, IL-10, F2, MPO, etc. (p > 0.05). Conclusion TMP is effective in the treatment of OA, with multi-target and multi-pathway interactions. ESR1, CAT, C3, CYP3A4, CYP2C9, and ANXA1 may be potential targets for TMP treatment of OA. The molecular mechanism mainly involves the formation of neutrophil extracellular trap, regulation of the actin cytoskeleton, complement and coagulation cascades, and T cell receptor signaling pathways, etc.